The Influence of Learning Techniques And Reading Interest on the Reading Comprehension Ability of Grade V Students of SDIT Al Hamidiyah Depok - Rerin Maulinda (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the influence of reading learning techniques and reading interest on the reading comprehension ability of grade V students. The learning models studied are Survey, Question, Read, Recite, and Review (SQ3R) and Direct Reading Thingking Activity (DRTA) reading learning techniques. SQ3R and DRTA are one of the techniques in learning reading. The SQ3R technique is used to improve reading comprehension skills in each student. While the DRTA technique is used to demand and train students to concentrate on understanding the content of the reading well. Both techniques are used to find out good techniques in reading comprehension. This research was conducted at SDIT Al Hamidiyah Depok with a sample of 80 students taken randomly. The research design used was factorial 2 X 2 and the technique used for hypothesis testing was two-track ANAVA followed by the Tuckey Test. The results obtained in this study are 1) There are differences in reading comprehension skills between students who learn with the SQ3R technique and students who learn with the DRTA technique; 2) There is a difference in reading comprehension skills in students with high reading interest between those who study with the SQ3R technique and those who learn with the DRTA technique; 3) There is a difference in reading comprehension skills in students with low reading interest between those who study with the SQ3R technique and those who learn with the DRTA technique; 4) There is an influence of interaction between learning techniques and reading interest on reading comprehension skills. Based on the results of the study, it can be concluded that the Survey, Question, Read, Recite, and Review (SQ3R) reading learning technique is better or more effective than the Direct Reading Thingking Activity (DRTA) technique. Interest in reading affects students' reading comprehension skills.